2006
DOI: 10.1080/00207230600963866
|View full text |Cite
|
Sign up to set email alerts
|

Field comparison of two Total Suspended Particulates (TSP) samplers to assess spatial variation

Abstract: In 2004, through the assistance of the World Bank, air quality monitoring equipment was supplied from the United Kingdom and United States to Edo State Ministry of Environment in Nigeria. Amongst the air pollution assessment tools supplied, are a portable SKC 506673 high volume Gravimetric Sampler and a light-scattering method -Haz-Dust ™ 10 µm particulate monitor -for airborne particles. In this preliminary study, the two samplers were co-located at different monitoring sites in Benin City to assess spatial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This study also included a projection of NO 2 concentration for 2005 and 2010. Further studies that showed the successful use of NO 2 passive samplers in European urban areas were published by Ukpebor et al (1999) and Lozano et al (2009). In Pakistan, a study of NO 2 monitoring was conducted in 2006.…”
Section: Introductionmentioning
confidence: 98%
“…This study also included a projection of NO 2 concentration for 2005 and 2010. Further studies that showed the successful use of NO 2 passive samplers in European urban areas were published by Ukpebor et al (1999) and Lozano et al (2009). In Pakistan, a study of NO 2 monitoring was conducted in 2006.…”
Section: Introductionmentioning
confidence: 98%
“…Ukpebor et al [6]), but also to locate point source, or to evaluate and test engineering controls. Furthermore the respirable fraction of airborne dust is useful in evaluating exposure of workers involved in dusty activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, eqn (4) may be expressed more compactly as (5) and introducing a further constant K″, airborne concentration assessment may be summarized as follows: (6) in which the influence on concentration readings of both mean mass average diameter and density are clearly identified.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to density, values are, respectively, 2.65 g/cm 3 for the test dust and 2.79 g/cm 3 for measured dust, whereas the average mass diameter values are 4.5-5 µm (test dust) and 4.3 µm (basalt dust), respectively. Considering eqn (6), and remembering that the efficiency of the optical particle detection system was not tested, and consequently neither was the N(I) parameter, these data would seem to be the main cause of the overestimation. In fact, the calibration factor, assessed by comparing the two sets of values, was found to be 0.91 and, the 'experimental ratio' between the basalt dust and the test dust was <1.…”
Section: Data Presentation Of the First Sampling Campaignmentioning
confidence: 99%
See 1 more Smart Citation